The Relationship between Quality of Life and Health Locus of Control Beliefs in Hemodialysis Patients - Jaleh Mohammad Aliha (Iran University of Medical Sciences, 2015)
Background: Chronic kidney disease as a major health problem can create physical, psychological, economic, and social problems for patients and generally affect their quality of life. However, health beliefs and behaviors of these patients can affect their health condition too. The purpose of this study was to determine the relationship between the quality of life and health locus of control beliefs in hemodialysis patients.  Methods: A cross-sectional correlation research design was used to conduct the study. The research population included all hemodialysis patients admitted to Shahid Hashemi Nejad Hospital. One hundred hemodialysis patients were recruited by convenience sampling. The patients' information was collected from their medical records. The WHO quality of life (WHOQoL) questionnaire and multidimensional health locus of control scale (MHLC) were used to collect data about main variables of the study. The data were analyzed by SPSS 16 software using descriptive and inferential statistics.  Results: The mean and standard deviation of quality of life score was 48.7±14.7 the highest mean score was reported for environmental satisfaction domain (60±21), and social domain received the lowest mean score (44±24). The mean and standard deviation related to health locus of control beliefs was 53±11. There was a statistically significant relationship between the quality of life and health locus of control beliefs (P=0.008), but the correlation was weak (r=0.2).  Conclusion: The quality of life has a significant correlation with health locus of control beliefs. Therefore, it is necessary to provide hemodialysis patients with education to improve and modify their health awareness and attitude.